Assessment of certain biomarkers for predicting survival in response to treatment in dogs naturally infected with canine parvovirus. (December 2020) - Eregowda, Chethan Gollahalli; De, Ujjwal Kumar; Singh, Mithilesh; Prasad, Hridayesh; Akhilesh,; Sarma, Kalyan; Roychoudhury, Parimal; Rajesh, Justus Babykutty; Patra, Manas Kumar; Behera, Suvendu Kumar
Abstract: Canine parvovirus (CPV) enteritis is an important cause of morbidity and mortality in puppies despite aggressive treatment. Identification of reliable biomarkers for CPV enteritis is essential to determine the severity, duration of hospitalization, and predict the clinical outcome. Meanwhile, the biomarkers will assist in decision-making with clients about the further course of treatment or euthanasia. The present study was conducted to evaluate the changes of total leukocyte count (TLC), neutrophil count, and serum concentrations of creatine kinase-MB (CK-MB), lactate dehydrogenase (LDH), intestinal fatty acid binding protein-2 (IFABP-2), albumin, ceruloplasmin (Cp), cortisol, free triiodothyronine (FT3 ) and free thyroxine (FT4 ) in survivors and non-survivors as a predictor of the clinical outcome. Marked leukopenia, neutropenia, hypoalbuminemia, elevated levels of CK-MB, IFABP-2, Cp, and cortisol were noticed in CPV-infected dogs than healthy dogs but, LDH, FT3 and FT4 concentrations did not differ significantly. The CPV-infected non-survivors had persistent leukopenia, neutropenia and elevated CK-MB, IFABP-2, Cp and cortisol concentrations at 72 h of commencement of treatment. In CPV-infected survivors, TLC and neutrophil count were significantly increased, and CK-MB, IFABP-2, Cp and cortisol concentrations were significantly decreased at 72 h of commencement of treatment. The positive predictive values (PPVs) for survival using cut-off value of TLC (>3.2 × 10 3 /μL), neutrophil count (>1.65 × 10 3 /μL), CK-MB (≤234.50 U/L), IFABP-2 (≤7.61 ng/mL), Cp (≤0.605 g/L) and cortisol (≤16.90 ng/mL) were determined as 89.47%, 88.88%, 94.73%, 93.33%, 94.44% and 89.47%, respectively with better area under receiver operating characteristic (ROC) curve as well as sensitivity. The magnitude of decrease in TLC, neutrophil count, and increase in CK-MB, IFABP-2, Cp and cortisol concentrations at 72 h of initiation of treatment in dogs with parvoviral enteritis could be useful indicators for the prognosis of the disease. Based on sensitivity (%) and specificity (%) from ROC curve analysis and PPV (%), it is concluded that serum CK-MB concentration will serve as the most useful biomarker followed by Cp and absolute neutrophil count. Highlights: Changes of certain biomarkers in blood and serum were examined in CPV enteritis as potential prognostic markers.. The CK-MB followed by ceruloplasmin and neutrophil count serves as suitable biomarker to predict the survivability and outcome of disease. The cut-off and positive predictive values of each marker at 72 h post treatment have also been established.